Les femmes, l’entreprise et le droit 2019: une décennie de réformes - World Bank Group (World Bank, 2019)
The World Bank Group’s Women, Business and the Law examines laws and regulations affecting women’s prospects as entrepreneurs and employees across 187 economies. Its goal is to inform policy discussions on how to remove legal restrictions on women and promote research on how to improve women’s economic inclusion. Women, Business and the Law 2019: A Decade of Reform introduces a new index measuring legal rights for women throughout their working lives in 187 economies. The index is composed of 35 data points grouped into eight indicators. The data covers a 10-year period not only to understand the current situation but to see how laws affecting women’s equality of opportunity have evolved over time. The index assesses economic rights at milestones spanning the arc of a woman’s working life: the ability to move freely; starting a job; getting paid; legal capacity within marriage; having children; running a business; managing assets; and getting a pension.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; droits des femmes*; entrepreneuriat; femmes*; périodes historiques; sciences de la gestion; thématiques; économie; égalité des sexes